JALAN PEMBARUAN ITU MASIH PANJANG. Sebuah Refleksi Mengenai Dampak Paradigma Baru Konsili Vatikan II Bagi Gereja Protestan (GMIT) - Mery Kolimon (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2013)
The Second Vatican Council is not just an important moment in the history of the Catholic Church, but for all Christian Churches. The conciliar moment was an integral part of verbum dei, a divine statement, which was not only spoken to the Catholic Church but to the entire Body of Christ, including the Protestant Churches. This essay highlights a number of issues regarding the impact the council has had on the renewal of Protestant Churches, in particular the Protestant Church in Timor (GMIT) including our understanding of the Church’s mission, ecumenical relations, the development of contextual theology, and also about the place and role of women in the Church. Kata-kata kunci: Konsili Vatikan II, misi Gereja, ekumenisme, teologi kontekstual, perempuan dalam Gereja.